Horizontal well’s path planning: An optimal switching control approach - Gong, Zhaohua; Teo, Kok Lay; Liu, Chongyang; Feng, Enmin (Applied mathematical modelling, 2015)
In this paper, we consider a three-dimensional horizontal well’s path planning problem, where the well’s path evolves as a combination of several constant-curvature smooth turn segments. The problem is formulated as an optimal switching control problem subject to continuous state inequality constraints. By applying the time-scaling transformation and constraint transcription in conjunction with local smooth approximation technique, the optimal switching control problem is approximated by a sequence of optimal parameter selection problems with only box constraints, each of which is solvable by gradient-based optimization techniques. The optimal path planning problems of the wells Ci-16-Cp146 and Jin27 in Liaohe oil field are solved to demonstrate the applicability of the approach proposed.